(untitled) (Fiep Bulletin - online, 2011)
Introduction: The quality of life was defined as "the individual’s perception about their position in life, in the context of culture and value systems in which he lives, and in relation to their objectives, expectations, patterns and concerns", any amendment that would lead to changes in quality of life, such as amputation, makes the individual change its interaction with society, this worsening when, in addition to have to face an amputation the individual is to live with the pain phantom. Pain or dormancy in a region that there is, I raise the compromising its self-esteem and often in a state of secession, denying acting directly on their quality of life. Objective: To verify changes in quality of life arising from the pain patients phantom amputees after conviviality with pain, changes in relation to the functional capacity, limitation of physical aspect, emotional, pain, general health status vitality, social and mental health. Methodology: held-if application of the SF-36, fitted with the objective to relate the amputation and pain phantom. THE instrument was applied to 25 patients amputees trans-femoral and trans-tibial treated in the Center for the rehabilitation of Faculty Assisi Gurgacz, in the period July to July 2010. Results: After the application of the questionnaire, were observed that 56% of interviewees exhibit compromise topic maximum limitation by physical aspect, but only 40% presented compromising quality of life, with characteristic incapacitating for pain and 100% of the sample presented more than 75% in the field of general state of health and social aspects.